Effect of Cinnamon Oil on Quorum Sensing-Controlled Virulence Factors and Biofilm Formation in Pseudomonas aeruginosa - Kalia, Manmohit (Public Library of Science, 2015)

(untitled) (PLoS One)
Quorum sensing (QS) is a system of stimuli and responses in bacterial cells governed by their population density, through which they regulate genes that control virulence factors and biofilm formation. Despite considerable research on QS and the discovery of new antibiotics, QS-controlled biofilm formation by microorganisms in clinical settings has remained a problem because of nascent drug resistance, which requires screening of diverse compounds for anti-QS activities. Cinnamon is a dietary phytochemical that is traditionally used to remedy digestive problems and assorted contagions, which suggests that cinnamon might contain chemicals that can hinder the QS process. To test this hypothesis, the anti-QS activity of cinnamon oil against P. aeruginosa was tested, measured by the inhibition of biofilm formation and other QS-associated phenomena, including virulence factors such as pyocyanin, rhamnolipid, protease, alginate production, and swarming activity. To this end, multiple microscopy analyses, including light, scanning electron and confocal microscopy, revealed the ability of cinnamon oil to inhibit P. aeruginosa PAO1 biofilms and their accompanying extracellular polymeric substances. This work is the first to demonstrate that cinnamon oil can influence various QS-based phenomena in P. aeruginosa PAO1, including biofilm formation.